2007
DOI: 10.3928/1081-597x-20070901-08
|View full text |Cite
|
Sign up to set email alerts
|

LASEK and Photorefractive Keratectomy for Myopia: Clinical and Confocal Microscopy Comparison

Abstract: PURPOSE: To compare postoperative visual acuity and corneal morphology after laser epithelial keratomileusis (LASEK) versus photorefractive keratectomy (PRK) in the correction of low to moderate myopia. METHODS: In a double-blind, randomized clinical trial, 50 myopic patients (mean: -4.5±1.35 diopters) were randomized to receive LASEK in one eye and PRK in the fellow eye. No mitomycin C eye drops were used in this study. Patients were observed daily for 4 days, then at 1 month and every 3 months up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…Previous studies have also reported higher grades of haze after traditional PRK compared to LASEK, particularly in the early postoperative months [13, 13]. Similar to our results, Ghirlando et al [3] reported a less intense wound healing process after LASEK than after traditional PRK, documented with confocal microscopy.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have also reported higher grades of haze after traditional PRK compared to LASEK, particularly in the early postoperative months [13, 13]. Similar to our results, Ghirlando et al [3] reported a less intense wound healing process after LASEK than after traditional PRK, documented with confocal microscopy.…”
Section: Discussionsupporting
confidence: 91%
“…16 Subsequent developments in refractive surgery (PRK, LASIK, laser epithelial keratomileusis [LASEK], epi-LASIK, femto-LASIK, and mitomycin C treatment) have resulted in increasingly better and faster wound healing after both hyperopic and myopic procedures. 5,6,[17][18][19][20] Along with this, the magnitude of stromal opacities in surgeries with newer laser technology has notably diminished. However, new techniques may cause new types of wound healing processes and haze formation, which need to be standardized and quantifi ed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the decision to reposition or to remove the epithelial flap seems a crucial difference, and some studies comparing the 2 methods have been performed. 35,38,[48][49][50] Prospective clinical studies comparing techniques are shown in Table 3 30,[38][39][40]44,46,47,[51][52][53][54][55][56][57] and laboratory studies in Table 4. 32,58,59 However, these studies yielded partly contradictory conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Potential differences in surface ablation techniques may be more obvious with higher degrees of correction, as reported years ago. [55][56][57][67][68][69] (4) Between the 4 groups, each consisting of 20 eyes, we performed 9 comparison tests at 1, 2, and 4 days and 21 comparison tests at 3 months. A P value less than 0.05 was considered statistically significant in this study, which corresponds In epi-LASIK, the lamina densa and lamina lucida were preserved and the hemidesmosomes had normal morphology.…”
Section: Discussionmentioning
confidence: 99%